Anxiety and depression in parents of disabled children - Sălceanu, Claudia; Sandu, Mihaela Luminita (Technium Social Sciences Journal, 2020)
Having a disabled child can add new challenges for parents and can affect, in different ways, the entire family and its way of life. Two of the most frequent consequences of having to take care of a disabled child are anxiety and depression. A sample of 30 adults (15 parents with disabled children and 15 parents with normal children) has been assessed with Beck Depression Inventory and with Cattell’s Anxiety Questionnaire. The main objectives of the study aim to identify if there are significant differences between the two categories of parents regarding anxiety and depression, and if there is a significant statistical correlation between the two personality traits. The results show higher anxiety and depression levels for parents of disabled children, and a significant correlation between the two traits. The practical implications of the study are discussed in the end.